Generalized t‐statistic for two‐group classification. Issue 2 (30th October 2014) - Komori, Osamu; Eguchi, Shinto; Copas, John B.
Summary In the classic discriminant model of two multivariate normal distributions with equal variance matrices, the linear discriminant function is optimal both in terms of the log likelihood ratio and in terms of maximizing the standardized difference (the t‐statistic) between the means of the two distributions. In a typical case–control study, normality may be sensible for the control sample but heterogeneity and uncertainty in diagnosis may suggest that a more flexible model is needed for the cases. We generalize the t‐statistic approach by finding the linear function which maximizes a standardized difference but with data from one of the groups (the cases) filtered by a possibly nonlinear function U. We study conditions for consistency of the method and find the function U which is optimal in the sense of asymptotic efficiency. Optimality may also extend to other measures of discriminatory efficiency such as the area under the receiver operating characteristic curve. The optimal function U depends on a scalar probability density function which can be estimated non‐parametrically using a standard numerical algorithm. A lasso‐like version for variable selection is implemented by adding <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj143qrnkz" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />L1</alternatives>‐regularization to the generalized t‐statistic. Two microarray data sets in the study of asthma and various cancers are used as motivating examples.